Studi Evaluasi Ekonomi Teknik Pembangunan Pasar Temanggung Jayakarti Tamiyang Layang: Economic Evaluation Study Of Development Techniques For The Temanggung Jayakarti Tamiyang Layang Maket - Hudan Rahmani; Nova Abriano; Silfiana Ila Masruroh; Noor Jasmani (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The fire disaster that befell most of the Jayakarti Temanggung Market on June 26, 2005, resulted in reduced service facilities. Before a fire occurs, indeed the Temanggung Jayakarti Market needs to be renovated because the building is quite old. The development of the city of Tamiang Layang is currently quite rapid accompanied by the demands of the dynamics of the behavior of consumers as consumers which also increased so that the Temanggung Jayakarti Market is now considered less attractive. This situation raises an idea to make efforts to organize and rebuild the Jayakarti Temanggung Market. Redevelopment and revitalization of the Temanggung Jayakarti Market is basically very good, and this will support the economic sector in the city of Tamiang Layang so that it will increase local revenue (PAD). Besides that, it can also attract attraction for outside regional investors to enter Tamiang Layang City. The purpose of writing is to find out whether the redevelopment and revitalization carried out by the Temanggung Jayak Market in technical economy.